Lifestyle Causing Low Sperm Quality : Literatur review - Aqilah Maharani; Fikri Rizaldi (Indonesian Andrology and Biomedical Journal, 2026)
Background : Infertility is a problem experienced by millions of couples around the world that affects various aspects of life. Infertility itself is a disease of the reproductive system that causes couples to fail to achieve pregnancy after having regular sexual intercourse without contraception for one year. The causes vary from the level of fertility in each individual in the couple and an unhealthy lifestyle can be one of the causes of infertility. Reviews : The factors that cause infertility are influence by lifestyle. Food consumption can have a negative impact on antioxidant content that affects fertility. Smoking, caffeine, obesity, psychological stress, and age can affect fertility due to the formation of oxidative stress that can affect sperm quality. Summary : Lifestyle affects fertility level, especially in men. Overall, changes such as a balanced diet, quitting smoking, increasing physical activity, maintaining weight, and managing stress are very important to support fertility and reproductive health.